2020
DOI: 10.1371/journal.pone.0229128
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the hip joint capsular complex: A systematic review of histological and immunohistochemical studies and their clinical implications for contemporary treatment strategies in total hip arthroplasty

Abstract: The hip joint capsule contributes to the stability of the hip joint and lower extremity, yet this structure is incised and often removed during total hip arthroplasty (THA). Increasing incidence of osteoarthritis is accompanied by a dramatic rise in THAs over the last few decades. Consequently, to improve this treatment, THA with capsular repair has evolved. This partial restoration of physiological hip stability has resulted in a substantial reduction in post-operative dislocation rates compared to convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The anterior capsule has been found to have the highest density of sensory nerve fibers in the hip joint [ 16 , 17 ]. A recent review of histological studies examining the innervation of the hip joint capsular complex shows that the posterior aspect of the capsule has a much lower density of sensory nerves than the anterior aspect of the capsule [ 18 ]. Furthermore, it has been previously shown that nociceptive hip joint capsule fibers primarily innervate the anterior aspect of the capsule, while the nerve fibers innervating the posterior aspect of the capsule are mainly mechanoreceptors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anterior capsule has been found to have the highest density of sensory nerve fibers in the hip joint [ 16 , 17 ]. A recent review of histological studies examining the innervation of the hip joint capsular complex shows that the posterior aspect of the capsule has a much lower density of sensory nerves than the anterior aspect of the capsule [ 18 ]. Furthermore, it has been previously shown that nociceptive hip joint capsule fibers primarily innervate the anterior aspect of the capsule, while the nerve fibers innervating the posterior aspect of the capsule are mainly mechanoreceptors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Schematic diagram of cervical sensorimotor control been reported in human cervical facet joints [23,24] and discs [25,26]. As with the peripheral joints [27,28], there are only a small number of mechanoreceptors in the lumbar and cervical facet joints [23,24]. There was no significant difference in the distribution of receptors between the upper and lower cervical facet capsules [24].…”
Section: Distribution Of Cervical Proprioceptorsmentioning
confidence: 99%
“…Overall, the density of mechanoreceptors in the joint capsule is low, but in the joint capsule of osteoarthritis patients it is lower. The density of mechanoreceptors in patients with osteoarthritis is 0.044 per mm 2 , and in healthy people is 0.053 per mm 2 [27,28]. Recently, a comparative study by Yang et al [25] found that Ruffini corpuscles were obviously increased in number and deeply ingrown into inner annulus fibrosus and even into nucleus pulposus in the diseased cervical discs from cervical spondylosis patients with dizziness in comparison with the discs from patients without dizziness and control discs.…”
Section: Density Changes Of Cervical Proprioceptorsmentioning
confidence: 99%
“…Notwithstanding the importance of pharmacologic and surgical interventions, their limitations remain stumbling blocks for many to a high life quality. In this respect, and in recognition of the limited and fragmented database in this regard, it is concluded that to improve upon our understandings of the origins of hip osteoarthritis pain, future high quality well-conceived and adequately funded clinical and basic research studies that explore whether an endogenous pain modulation impairment is a significant contributor to hip osteoarthritis pain [90], along with any possible descending neural pathway dysfunction, plus the role of brain specific pain activity [75] [91] and hip joint mechanoreception [92] in this disease, topics not well studied, will be extremely helpful and are strongly encouraged.…”
Section: Discussionmentioning
confidence: 99%